The Effect of Axial Magnetic Field on The Breakdown Voltage of Air at Low Pressure - Owaid, Ahmed; Owaid, Ahmed Y. (Iraqi Journal of Science, 2020)
To add more details about the effect of the axial magnetic field on the plasma profile, the breakdown voltage of air was investigated at low pressure (9-15 Pa) in the presence of axial magnetic field (0.01-0.04T). The air was ignited by a DC voltage between two plain electrodes of aluminum separated by a distance (8.5cm). The measurements showed that the discharge voltage decreases to a minimum value, then returns to increase over the minimum with increasing the magnetic field strength, at all pressures in the range. It was also observed that a maximum decrease in the discharge voltage is obtained near the minimum of Paschen curve from the right side. The decrease in the discharge voltage was caused mainly by the effect of magnetic flux density on the diffusion of charged particles to the walls, especially on that of free electrons which were borne during the breakdown process.